Exploring Stressors of the University Faculty members: A Comparative Study - Alboliteeh, Mohammad (Advances in Social Sciences Research Journal, 2019)
Stress is defined as a dynamic condition in which an individual is confronted with an opportunity, constraint, demand related to what he or she desires and for which the outcome is perceived to be both uncertain and important. This study focused on the manifestations and the sources of stress on faculty members of Hail University for the 2nd Semester of Academic Year 2018-2019. A quantitative-comparative approach was employed in this study. There were 236 faculty who had participated in the study resulting to 94.4% response rate. Data collection started from February 2019 to April 2019. To measure manifestations and the sources of stress, the Total Teacher Concern Inventory was used. This consists of 48 distinct statements. Weighted mean, Analysis of Variance (F-test), and (t-test) were used. All statistical analyses were performed at 0.05 level of significance. Results shows that the faculty disagreed that the sources of stress from work-related stressors (3.47). A significant difference between time management and sex (0.04) was determined. Likewise, a significant difference between gastrointestinal manifestations (0.01), behavioral manifestations (0.01) and the faculty’s age was obtained.